2021
DOI: 10.1007/s40618-021-01669-3
|View full text |Cite
|
Sign up to set email alerts
|

Glucose control in home-isolated adults with type 1 diabetes affected by COVID-19 using continuous glucose monitoring

Abstract: Purpose This study is aimed at evaluating changes in metrics of glucose control in home-isolated patients with type 1 diabetes and COVID-19 using a continuous glucose monitoring (CGM) system. Methods We included adults aged 18–45 years with type 1 diabetes, using CGM, followed by telemedicine at a Southern Italian University Hospital. Thirty-two home-quarantined subjects with SARS-CoV-2 positive swab constituted the COVID-19 group. Thirty age-matched diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Blood glucose levels were restored in a fairly short time to previous levels, coinciding with the end of the viral infection. A similar observation was reported among 32 adults with T1D during the infection period ( 33 ). Thus, COVID-19 infection among young people with T1D probably resembles the effects of other viral infections during sick days ( 34 ).…”
Section: Discussionsupporting
confidence: 88%
“…Blood glucose levels were restored in a fairly short time to previous levels, coinciding with the end of the viral infection. A similar observation was reported among 32 adults with T1D during the infection period ( 33 ). Thus, COVID-19 infection among young people with T1D probably resembles the effects of other viral infections during sick days ( 34 ).…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, the restriction of the survey to a cohort of T1D patients followed by a single center and mainly from the Liguria region limits the generizability of the results. Our study shows high patient and parental satisfaction, probably also related to the efficacy of the new technological devices and to the correct management of diabetes, which was not limited by the follow-up via televisits ( 29 , 30 ). The strength of our study is that, to our knowledge, it is the first survey focused on patient satisfaction of telemedicine in a pediatric and young population with type 1 diabetes.…”
Section: Discussionmentioning
confidence: 60%
“…We would like to share ideas on "Glucose control in homeisolated adults with type 1 diabetes affected by COVID-19 using continuous glucose monitoring [1]." Longo et al concluded that "Young home-isolated patients with type 1 diabetes and COVID-19 showed a worsening of …infection [1]." In general, COVID-19 can affect glucose metabolism and it might result in elevation of blood glucose and hemoglobin A1C [2].…”
Section: Dear Editormentioning
confidence: 99%